2020
DOI: 10.1186/s43014-020-00022-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods and parameters on the antioxidant properties of tea (Camellia sinensis) leaves

Abstract: Background: Conventional drying using heated air oven is commonly used as a method for preserving the product but often affects the nutritional value, taste, and texture. However, the heat from the drying method can oxidize and destroy heat-sensitive compounds. Superheated steam (SHS) drying uses superheated steam instead of hot air or combustion gases in a direct dryer and was reported better at preserving the nutritional values of food products. Aim: To evaluate the effect of SHS drying on antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
4
18
0
1
Order By: Relevance
“…The primary structure of dried leaves was preserved during drying due to the developed frozen water molecules or ice crystal within the leaf tissue matrix has lower movement compared to its liquid form [ 31 ]. This present finding was in agreement with a recent study by Roslan et al [ 32 ], as the freeze-dried leaves of Camellia sinensis or authentic tea showed the highest phenolics, flavonoids, and antioxidant activity compared to superheated steam and oven drying techniques.…”
Section: Discussionsupporting
confidence: 94%
“…The primary structure of dried leaves was preserved during drying due to the developed frozen water molecules or ice crystal within the leaf tissue matrix has lower movement compared to its liquid form [ 31 ]. This present finding was in agreement with a recent study by Roslan et al [ 32 ], as the freeze-dried leaves of Camellia sinensis or authentic tea showed the highest phenolics, flavonoids, and antioxidant activity compared to superheated steam and oven drying techniques.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding treatments, on average, OD samples showed significantly lower TPC than FD ones (−82%), as also observed in the literature data on different plant matrices [ 47 , 48 ]. Among FD samples, Chinook showed the highest TPC (V1; 39 ± 1 mg GAE g −1 ), followed by Columbus (V4; 35.9 ± 0.8 mg GAE g −1 ) and Cascade (V5; 28.9 ± 0.2 mg GAE g −1 ).…”
Section: Resultssupporting
confidence: 84%
“…However, oven drying showed a detrimental effect on retaining phenolic and flavonoids content when drying at higher temperature (> 100 °C). Therefore, it is better to limit the oven drying temperature to not more than 100 °C as observed in a tea product [11].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Regarding the preparation of dried Mekai, gas and electric drying can be utilized as the technologies are readily available in the market. Furthermore, the drying method may play a role in the active substance and amino acid contents of Mekai leaf, as indicated from research with other leaves [10,11]. Therefore, this research aims to characterize moisture, ash, protein, polyphenolic, flavonoids, amino acid contents, and the antioxidant capacity of Mekai leaves dried with sun exposure, gas, and electric oven at various temperatures and times.…”
Section: Introductionmentioning
confidence: 99%